The Involvement of The United States in the Russia-Ukraine war in The Perspective of Realism - Nurwulan Rizkiya Anjani; Arie Kusuma Paksi (AEGIS : Journal of International Relations, 2023)
This paper examines the involvement of the United States in the Russia-Ukraine war. One of the main topics of study in Cold War studies is how the United States interacted with and intervened in various domestic affairs of nations in different regions of the world between the 1950s and the 1970s.  States interact with one another in particular through international relations. Realists view international politics as fundamentally a contest between superpowers over dominance and security. During the cold war, Russia and Ukraine were united in a federated state, the Soviet Union. And in 2022, the conflict between Russia and U kraine is heating up again, and the United States will be involved here. However, this study focuses on the involvement of the United States in the Russo-Ukrainian war, which is analyzed with one of the main theories in international relations, realism. Realism theory focuses on the potential for conflict between state actors, particularly relevant to the conflict between Russia and Ukraine. This research employs a qualitative methodology with a literature review, in which the author gathers data pertinent to the subject under consideration. The result of this research is the involvement of the United States in the war between Russia and Ukraine is part of their tactics to maintain their hegemony as the only superpower in the post-cold war world.